KINERJA KEUANGAN DAN REPUTASI PERUSAHAAN: STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Oktavianus, Laurentius Christian; Randa, Fransiskus; Jao, Robert; Praditha, Riza (KRISNA: Kumpulan Riset Akuntansi, 2022)
The purpose of this study is to investigate the effect of financial performance on company reputation and the influence of company reputation on financial performance. This study uses secondary data, namely the annual report and Corporate Image Index (CII) visited by the Frontier Consulting Group. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange which have a CII score index consecutively during the 2016-2019 period. The number of companies that meet the criteria in this study are 34 companies selected using purposive sampling with a total of 136 data observed. This study uses simple linear regression analysis. The results of this study indicate that financial performance has a positive and significant effect on the company's reputation and the company's reputation has a positive and significant effect on financial performance.